Picker Wheel sebagai Media Digital Inovatif untuk Penguasaan Materi Al-Qur’an Berbasis Gamifikasi di Madrasah Ibtidaiyah - Marwah, Marwah; Marhani, Marhani; Saleh, Muhammad; Amin, Sitti Jamilah; Usman, Usman (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
The implementation of the Picker Wheel media serves as an innovative alternative in Qur’an learning at Madrasah Ibtidaiyah. This media has rarely been applied in the context of Qur’anic instruction, making this study one of the early efforts to examine its effectiveness in improving students’ mastery of learning materials. The main objective of this study is to identify the differences in students’ mastery levels before and after learning using the Picker Wheel, as well as to evaluate the effectiveness of this media in supporting learning outcomes. This research employed a quantitative approach with a one-group pretest-posttest design, involving all 30 third-grade students at Madrasah Ibtidaiyah Negeri Barru using a total sampling technique. Data were collected through written and oral tests, learning activity observation sheets, and documentation. The data were analyzed using descriptive and inferential statistics through a paired sample t-test. The results showed a significant improvement, with the average written test score increasing from 48.80 to 82.53, and the oral test score from 67.87 to 82.67. The significance value of 0.001 (< 0.05) indicates that the use of the Picker Wheel is effective in enhancing students’ mastery of Qur’anic materials. The implication of this study suggests that the Picker Wheel can be used as an engaging and interactive learning medium to improve students’ participation and learning outcomes in Qur’anic education at the elementary madrasah level.